IMPLEMENTASI YOGA KIDS UNTUK MENINGKATKAN KEBUGARAN DAN KONSENTRASI ANAK DALAM MENGHADAPI PEMBELAJARAN DI ERA MERDEKA BELAJAR - Palifiana, Dheska Arthyka; Khadijah, Sitti; Dewi, Devillya Puspita (Universitas Muhammadiyah Mataram, 2023)
Abstract: In the concept of independent learning, both teachers and students are subjects in the learning system. Learning in the era of independent learning requires students to be prepared for their physical and mental conditions so as to participate in learning along with good learning achievements. Good physical fitness of students is the basis for creating learning concentration and having good learning achievement. One way to improve children's fitness and concentration is through yoga kids. Yoga is an activity that directs a person to concentrate, regulate breath, and calm the mind with certain poses. The aims to improve children's fitness and concentration in learning through yoga kids. Methods: This research is a quasiexperimental study with pretest posttest desing. Sampling was carried out at Mahoni 2 Integrated Healthcare Post at Gedongkiwo Village, Yogyakarta City among 24 children aged 5-9 years. Yoga kids was performed 3 times for one week with a duration of 2 hours per meeting... Results and Discussion: Based on the characteristics of respondents, it was found that most of respondents were male (62.5%), 7 years old (33.3%), and had elementary education (66.7%). The results of the analysis using paired sample t-test obtained a p-value of 0.000<0.05, which meant that yoga kids could improve children's fitness and concentration. Conclusion: Yoga kids had a significant effect on the improvement of children's fitness and concentration.Abstrak: Dalam konsep merdeka belajar, antara guru dan murid merupakan subyek di dalam sistem pembelajaran. Dalam menghadapi pembelajaran di era merdeka belajar, siswa harus dipersiapkan kondisi fisik maupun mentalnya agar dapat mengikuti pembelajaran dan mendapatkan prestasi belajar yang baik. Salah satu cara untuk meningkatkan kebugaran dan konsentrasi anak yaitu dengan melakukan yoga kids. Yoga adalah sebuah aktivitas yang mengarahkan seseorang untuk berkonsentrasi, mengatur nafas, menenangkan pikiran dengan pose-pose tertentu. Tujuan penelitian mengetahu pengaruh yoga kids terhadap kebugaran dan konsentrasi anak. Metode penelitian: penelitian ini merupakan penelitian quasi eksperiment dengan pretest posttest design. Sampel dalam penelitian ini yaitu anak-anak usia 5-9 tahun sebanyak 24 anak di Posyandu Mahoni 2 Gedongkiwo Mantrijeron Yogyakarta. Pemberian yoga kids dilakukan sebanyak 3 kali selama satu minggu dengan durasi 2 jam per pertemuan. Hasil: karakteristik responden sebagian besar laki-laki (62,5%), berumur 7 tahun (33,3%), berpendidikan SD (66,7%). Terdapat pengaruh yoga kids terhadap kebugaran dan konsentrasi anak dengan p-value 0,000. Kesimpulan: Yoga kids secara signifikan dapat meningkatkan kebugaran dan konsentrasi anak.